Evaluation of a lens-free imager to facilitate tuberculosis diagnostics in MODS - Solis L. (2016)
Tuberculosis (TB) control efforts are hampered by a mismatch in diagnostic technology. Lack of adequate early diagnostics and Multi-drug resistant (MDR) detection is a critical problem in control efforts. Alternate and novel diagnostic approaches are required, especially in low-resources settings where they are needed most. The Microscopic Observation Drug Susceptibility (MODS) assay is a cost-effective, highly sensitive, and specific method based on the detection of characteristic cording growth patterns of Mycobacterium tuberculosis (MTB), in microscopic examination of a liquid culture under an inverted microscope. By adding antimicrobials to the wells, MODS also determines antimicrobial susceptibility in both MDR and Extreme Drug Resistant (XDR) tuberculosis. The interpretation of a MODS culture performed in a 24 well plate, requires an extensive inspection over the entire surface to detect TB cords. This process requires significant time and effort from a trained microscopist. We evaluated a lens-free imager system, able to render microscopic images of live specimens, for the proof of principle to be used for MODS culture interpretation. The lens-free imager system is able to digitalize a 24-mm2 surface with approximately 40X magnification in a single capture. The evaluation of the lens-free imager found that it produced microscopic images that were adequate for MODS interpretation by a human expert. Compared to the average time that takes a microscopist to completely examine a MODS culture sample, the lens free imager notably reduced the time of inspection. Therefore, lens-free imager variants may constitute promising systems to aid in the diagnostics of tuberculosis, by simplifying and reducing the time of inspection and permitting automatization of MODS interpretation.